International scientific production on intrapreneurship: an analysis of research, frontiers and trends - Olívia Carolina de Resende Ribeiro; Elvis Magno da Silva; Neliva Terezinha Tessaro; Nelson Pereira Castanheira (Gestão & Produção)
Abstract The objective of this study is to conduct a bibliometric analysis of intrapreneurship and establish a future agenda. Intrapreneurship refers to terms, processes or practices that describe the entrepreneurial behaviors and orientations of individuals and corporations within existing organizations, which enable the performance of these organizations. The study employed a bibliometric methodology to collect data from the Web of Science. All years up to December 2021 were included in the database. The data was analyzed using CiteSpace software. To establish a future research agenda, we considered papers published in 2020 and 2021. The data indicates that: publications and citations have significantly increased since 2012; the debate is mainly concentrated in the United States; the works are interdisciplinary and multidisciplinary; the most referenced text by the articles in the database is Antoncic and Hisrich (2001); and finally, the narrative of intrapreneurship as a driving factor for organizational success dominates the field, despite its recent application. Thus, this study contributes to the field by providing a comprehensive analysis of the evolution of scientific production, highlighting the main studies and authors that have shaped its trajectory.